Synergistic toxicity of nanoplastics and Helicobacter pylori on digestive system in mice - Xiaolin Zhang; Yunqing Wang; Xiaohan Tong; Boqing Li; Sisi Liu; Yingzi Cui; Wenke Wang; Zhiqin Li; Chunlei Ma; Ying Zhang (Ecotoxicology and Environmental Safety)
Nanoplastics, in combination with pathogenic microorganisms or toxic substances, have been shown to induce oxidative stress and disrupt energy and lipid metabolism, posing significant health risks. This study evaluated the toxic effects of co-exposure to nanoplastics and Helicobacter pylori on the digestive system of mice. Transmission electron microscopy confirmed the accumulation of AuPS-NPs (Au-core polystyrene nanoplastics) in the stomach, colon, and liver, while hematoxylin and eosin staining revealed dose-dependent pathological damage in these tissues. Enzyme-linked immunosorbent assays quantified interleukin-6 (IL-6), malondialdehyde (MDA), triglyceride (TG), and lactate dehydrogenase (LDH) levels, which significantly increased in co-exposure groups compared to single-exposure groups (P < 0.05). After 28 days, the 100 mg/L H. pylori-AuPS-NPs group showed the highest levels of IL-6 (172.91 ± 1.51 pg/mL in the stomach, 188.31 ± 1.49 pg/mL in the colon, and 174.85 ± 0.26 pg/mL in the liver) and MDA (13.49 ± 0.16 nmol/mg in the stomach, 14.39 ± 0.20 nmol/mg in the colon, and 15.61 ± 0.63 nmol/mg in the liver). These increases, accompanied by elevated TG and LDH levels, suggest aggravated inflammation, oxidative stress, and metabolic disruption. Accumulation analysis showed that while AuPS-NPs content significantly increased over time and with higher concentrations, co-exposure with H. pylori reduced nanoparticle accumulation in gastric and intestinal tissues. These results indicate that co-exposure exacerbates tissue damage, inflammation, oxidative stress, and metabolic disruptions while modulating nanoparticle accumulation. These findings highlight the synergistic toxic effects of nanoplastics and H. pylori, underscoring the importance of understanding combined exposure risks for public health.